Determinants of HIV infection at 18 months of age among HIV-exposed infants in the context of PMTCT interventions in southern Ethiopia - Israel, Eskinder; Astatkie, Ayalew; Taye, Kefyalew; Christou, Aliki; Lejore, Ephrem; Asefa, Anteneh (Frontiers in Reproductive Health, 2024)
IntroductionMother-to-child transmission (MTCT) of HIV accounts for over 90% of annual HIV infections among children under the age of 15. Despite the introduction of the Option B+ strategy in Ethiopia in 2013, the rate of MTCT of HIV at 18 months was 15% in 2020. This study aimed to identify determinants of HIV infection among HIV-exposed infants (HEIs) in the context of prevention of MTCT (PMTCT) care in southern Ethiopia.MethodsWe conducted a retrospective facility-based study of 299 mother-baby pairs (HIV-infected women and their HEIs up to 18 months) enrolled in PMTCT care at three health facilities in Wolaita Sodo town, southern Ethiopia, from September 2015 to October 2021. Data was collected from medical charts and PMTCT registers. Logistic regression was used to identify determinants of HIV infection among HEIs.ResultsAt enrolment into PMTCT care, most women were already on ART (75.3%) and in clinical stage I (89.6%) according to the World Health Organization's algorithm. Overall, 13 (4.3%, 95% CI: 2.5%–7.4%) HEIs were HIV-infected; the level was higher among HEIs born at home (17.9% (95% CI: 7.6%–36.5%). Being born to HIV-positive women with late WHO clinical stage (III and IV) of HIV (AOR = 9.1, 95%CI: 2.4, 34.5), being born at home (AOR = 4.8, 95%CI: 1.1–20.7), being born to women newly diagnosed with HIV (AOR = 4.8, 95%CI: 1.3–17.4), and low infant adherence to cotrimoxazole prophylaxis (AOR = 5.4, 95%CI: 1.4–20.4) increased the odds of MTCT.ConclusionHIV infection levels among breastfeeding HEIs in PMTCT care was <5%, meeting the WHO transmission rate targets. Strengthening PMTCT care to expand community-based PMTCT interventions such as improving women's and communities’ awareness of HIV, PMTCT and promoting male involvement would reduce reduce HIV infection among children to reach the 95–95–95 targets to end HIV in Ethiopia.